Epistemology Of Thematic Interpretation: A Comparison Of The Methodological Frameworks Of Al-Farmāwī And Abdullah Saeed - Khoirul Anas; Achmad Jazuli Affandi; Ahmad Fawaid (PT. Intelek Cendikiawan Nusantara, 2025)
This research examines the epistemology of thematic Qur’anic interpretation through a comparative analysis of the methodological frameworks developed by ‘Abd al-Ḥayy al-Farmāwī and Abdullah Saeed. The study aims to identify the epistemological similarities and differences between the two scholars, particularly regarding the sources of interpretive authority, the role of context, value orientation, and their methodological implications for contemporary thematic exegesis. Employing qualitative library research, this study applies an epistemological and comparative approach to the primary works of both scholars and relevant academic literature. The findings indicate that al-Farmāwī represents a textual-normative and systematic epistemology of thematic interpretation, emphasizing the internal coherence of Qur’anic verses. In contrast, Abdullah Saeed advances a contextual and value-oriented epistemology that highlights the dynamic interaction between the Qur’anic text, the historical context of revelation, and contemporary realities. Despite these differences, both approaches converge in their rejection of atomistic interpretation and their commitment to a comprehensive thematic method. This study argues that integrating textual coherence and contextual relevance offers a significant pathway for the further development of thematic Qur’anic interpretation in contemporary Islamic scholarship